Porphyrin Metalation at MgO Surfaces: A Spectroscopic and Quantum Mechanical Study on Complementary Model Systems. Issue 5 (18th December 2015) - Schneider, Johannes; Franke, Matthias; Gurrath, Martin; Röckert, Michael; Berger, Thomas; Bernardi, Johannes; Meyer, Bernd; Steinrück, Hans‐Peter; Lytken, Ole; Diwald, Oliver
Abstract: We show that both single‐crystalline and nanostructured MgO surfaces convert free‐base tetraphenyl porphyrin (2HTPP) into magnesium tetraphenyl porphyrin (MgTPP) at room temperature. The reaction can be viewed as an ion exchange between the two aminic protons of the 2HTPP molecule with a Mg 2+ ion from the surface. The driving force for the reaction is the strong stability of the formed hydroxyl groups along the steps and at defects on the MgO surface. We have used an integrated characterization approach that includes UV/Vis diffuse reflectance measurements on nanostructured powders, X‐ray photoelectron spectroscopic investigation of atomically clean MgO(100) single‐crystalline thin films, and density functional theory (DFT) calculations on model systems. The DFT calculations demonstrate that MgTPP formation is strongly exothermic at the corners, edges and steps, but slightly endothermic on terrace sites. This agrees well with the UV/Vis diffuse reflectance, which upon adsorption of 2HTPP shows a decrease in the absorption band associated with corner and edge sites on MgO nanocube powders. Abstract : Porphyrin swap shop : Spectroscopic adsorption studies on two complementary model systems, atomically clean thin MgO(100) films and MgO nanocube powders, show that low‐coordinated surface cations located in corner, edge, or step regions of the MgO surfaces are subject to ion exchange between adsorbed porphyrin molecules and the oxide surface.